A política de cotas na Universidade Tecnológica Federal do Paraná - Medeiros, Jussara Marques de (2015)
This work aims to analyze the impact of racial quotas policy implemented at the Federal Technological University of Paraná by means of Law No. 12,711 / 2012, from a gender and race perspective. This law provides for the entry of shareholders in federal universities and federal institutions of secondary and technical education. The research discusses the concepts of race and ethnicity and its historical construction, inequality and racial discrimination, relating to the concepts with the gender category and making a link between human rights and public policies, which are presented here as strategies of rights protection. The construction of this work started with the assumption that gender relations are socially and culturally constructed and thus contribute to courses in scientific and technological areas, that continue to be perceived as masculine, with differences in access considering white and black men and women. The selection of courses taking in consideration, sexual division present in higher education, given the fact that the engineering and degrees in the fields of Mathematics, Physics and Chemistry remain with a student body predominantly masculine. The survey was conducted from the data of the academic system graduates and graduates of engineering and degrees, shareholders and nonshareholders, for profile analysis of students and as brown and black self-declared students and their academic performance, in 2013 when it was established as Law No. 12.711/212 by 2015. Then, qualitative research through a sample was performed, that is, racial shareholders women who declared themselves black and brown to complement the quantitative data through questionnaire and interview.